Evidence for resistance of activated sludge flocs to deflocculative DO stress - Suresh, Akshaykumar (2021)
In the published literature, deflocculation of aerobic biological flocs under low dissolved oxygen (DO) (< 0.5  mg/L) conditions is typically reported as occurring as early as after 1 h of oxygen deficiency. However, results of this study involving aerobic sludge from three different sources repeatedly indicated a lack of deflocculation after 24 h of low DO conditions. This finding has led to the conclusion that low DO might not be a direct cause of deflocculation. In addition to the low DO conditions, the sludge samples were not re-fed throughout the experiment, but deflocculation was still not observed. An analysis of the soluble microbial products (SMP) and loosely and tightly bound extracellular polymeric substances (EPS) was performed to improve understanding of the sludge’s behavior in response to low DO conditions. Results indicated no increase in SMP content or change in the tightly bound EPS content upon extended periods of low DO. It was concluded that high proteins concentration in the bound EPS improved flocs stability, and so contributed to the maintenance of floc integrity during extended periods of low DO conditions.